Performance of the rapid triage conducted by nurses at the emergency entrance - Bruna Roberta Siqueira Moura; Lilia de Souza Nogueira (Universidade de São Paulo, 2020)
Objective: to compare the performance of the rapid triage conducted by nurses at the emergency entrance and of the Manchester Triage System (MTS) in identifying the priority level of care for patients with spontaneous demand and predicting variables related to hospitalization. Method: a cross-sectional study carried out in an Emergency Department (ED) of a university hospital in São Paulo. The priority levels established in the rapid triage performed by nurses were high priority (patients of spontaneous demand directed to the emergency room) or low priority (those referred to the institution's usual flow). Diagnostic accuracy measures were calculated to assess the performance of the indexes. Results: of the 173 patients (52.0% female, with mean age of 60.4 ± 21.2 years old) evaluated, it was observed that rapid triage was more inclusive for high priority and had better sensitivity and worse specificity than the MTS. The probability of non-severe patients being admitted to the emergency observation unit was lower due to the rapid triage. For the prediction of the other variables, the systems presented unsatisfactory results. Conclusion: the nurses overestimated the classification of patients as high priority, and rapid triage performed better than MTS in predicting admission to the emergency observation unit.